Design of earth-abundant Z-scheme g-C3N4/rGO/FeOOH ternary heterojunctions with excellent photocatalytic activity. Issue 9 (17th February 2021) - Arif, Nayab; Wang, Zhao-Xu; Wang, Yan-Tao; Dou, Yi-Chuan; Li, Kui; Liu, Shi-Quan; Liu, Fu-Tian
Abstract : A ternary Z-scheme g-C3 N4 /rGO/FeOOH heterostructure photocatalyst for H2 production was designed and fabricated, which exhibited photocatalytic H2 production of 124.9 and 869.8 μmol h −1 g −1 under visible and UV-Vis light irradiation, respectively. Abstract : Iron is one of the most abundant elements on the surface of the earth (5.1%), but is rarely used for photocatalytic hydrogen production due to its unsuitable band structure. Herein, a ternary Z-scheme g-C3 N4 /rGO/FeOOH heterostructure photocatalyst for hydrogen production was designed and fabricated. Due to its narrow bandgap and a low oxygen evolution overpotential of FeOOH, the Z-scheme g-C3 N4 /rGO/FeOOH ternary heterojunction exhibited excellent photocatalytic hydrogen production with the yields of 124.9 and 869.8 μmol h −1 g −1 (244.9 and 107.4 times larger than that of pristine g-C3 N4 ) under visible and UV-visible light irradiation, respectively. This work could expand the usage of the earth-abundant element for solar energy conversion and provide a new viewpoint for the development of high-performance photocatalysts through a rational design of the component of the heterostructure.